Technical, Economic and Societal Effects of Manufacturing 4.0 Automation, Adaption and Manufacturing in Finland and Beyond - Collan, Mikael; Michelsen, Karl-Erik (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
This open access book is among the first cross-disciplinary works about Manufacturing 4.0. It includes chapters about the technical, the economic, and the social aspects of this important phenomenon. Together the material presented allows the reader to develop a holistic picture of where the manufacturing industry and the parts of the society that depend on it may be going in the future. Manufacturing 4.0 is not only a technical change, nor is it a purely technically driven change, but it is a societal change that has the potential to disrupt the way societies are constructed both in the positive and in the negative. This book will be of interest to scholars researching manufacturing, technological innovation, innovation management and industry 4.0.